“One of the best advertising mediums the country can have:”: Postage Stamps and National Identity in Canada, New Zealand and Australia - Maloney, Michael (Material Culture Review, 2013)
Abstract This article examines the transformation of postage stamp imagery in Canada, New Zealand and Australia from the late 19th century to the 1990s. It documents the manner in which this imagery evolved from a predominately ethnic representation during the first half of the 20th century to a preponderance of civic–nationalistic designs in the post-1960s period. By highlighting the largely similar ways in which the governments of these three nations used postage stamps to guide and reflect the revision of their respective national identities, the article seeks to encourage greater comparative work among scholars examining the political and cultural histories of these nations. It also emphasizes the utility of recognizing postage stamps as rich primary sources of material culture that can facilitate comparative research that focuses on broad temporal and geographic parameters.